PHRASEOLOGICAL UNITS AND THEIR LINGUISTIC NATURE - Achilov Muzaffar Norkuliyevich (Bright Mind Publishing, 2026)
In this scientific article, the phraseological richness of the language, that is, the system of phrases, is closely related to such aspects as the consistency and hierarchical structure of language units. As we get acquainted with phraseological units, our ideas about the word and its meaning, the figurative meaning of the word, word groups and their grammatical categories, word combinations and the structure of sentences, and the expressive capabilities of language tools are formed more deeply.
Keywords: Phraseology, lexicon, phraseological unit, semantics.